Morphological description of early stages of 3 species belonging to Clupeiformes from the Kalong and Tien Yen estuaries, Vietnam - Hau, Tran Duc; Thao, Pham Thi (Academia Journal of Biology, 2017)
Fish species in the order Clupeiformes are economically important and to be conserved. However, in many species in this order, early developmental stages are either unknown or only partially known, especially in Vietnam. In the present study morphology of larvae and juveniles were examined for the Commerson’s anchovy Stolephorus commersonnii, the fringescale sardinella Sardinella fimbriata and the dotted gizzard shad Konosirus punctatus collected at the Kalong and Tien Yen Rivers between 2013 and 2015 in Viet Nam. Stolephorus commersonnii were postflexion larvae (accounted for 61.6% of total samples of this species) to juveniles (38.4%), ranging from 10.3 to 55.8 mm BL. Sardinella fimbriata were flexion (0.5%) to postflexion (99.5%) larvae, ranging from 4.7 to 23.8 mm BL. A total of 14 postflexion larvae of Konosirus punctatus (19.6-23.3 mm BL) were collected during the sampling period. Dorsal and anal fins tended to migrate anterior with growth are noticeable characteristics of these species. At around 23 mm BL, the anal-fin base was located behind the dorsal-fin one in Sardinella fimbriata and Konosirus punctatus, the pelvic-base behind the dorsal-fin one in Konosirus punctatus. Melanophores on the trunk were scarely developed in Stolephorus commersonnii and Sardinella fimbriata. These are important characteristics to identify the species in the order Clupeiformes for future researches.   Citation: Tran Duc Hau, Pham Thi Thao, 2017. Morphological description of early stages of 3 species belonging to Clupeiformes from the Kalong and Tien Yen estuaries, Vietnam. Tap chi Sinh hoc, 39(2): 155-164. DOI: 10.15625/0866-7160/v39n2.8303 *Corresponding author: hautd@hnue.edu.vn Received 7 May 2015, accepted 20 March 2017